POLA PENANGANAN KASUS STUNTING DI KECAMATAN KOTA RAJA SEBAGAI PENEGAKAN HAK ANAK MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Edison Natonis; Umbu Lily Pekuali; Norani Asnawi (Journal of Innovation Research and Knowledge, 2026)
Stunting remains a serious public health problem in Indonesia, particularly in Kupang City, where its prevalence threatens the fulfillment of children’s rights to optimal growth and development. This study aims to evaluate the success of stunting management as part of the fulfillment of children’s rights under Law No. 35 of 2014 on Child Protection, as well as to identify the factors influencing its handling in Kupang City. Using a qualitative approach, data were collected through in-depth interviews with mothers of stunted children, health workers, and community cadres, complemented by document analysis. The results show that stunting management in Kupang has made progress, particularly through nutrition programs, health services, and socialization efforts. However, implementation still faces challenges such as limited access to information, low community awareness, socio-economic constraints, and limited coordination between stakeholders. The study concludes that fulfilling children’s rights in the context of stunting management requires not only programmatic interventions but also structural improvements, including stronger inter-sectoral collaboration, sustainable community education, and integration of child protection principles into health policies.